iV-stem kit: stem magic balloon - Hanuar, Muhammad Naqib Afiq; Khamis, Ahmad Hakim; Mohd Esa, Nursyazliana; Fadzillah, Nur Camelia Arife; Hasan, Diana Nabila (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2023)
iV-STEM KIT: STEM MAGIC BALLOON is a high-impact product that was innovated to be used as a tool and teaching aid in the STEM field. This special product was created by a group of researchers from STEM volunteerism known as iV-STEM@VOLUNTEERS STEM because it was found that many primary school students are not interested in STEM-based subjects. Currently, the enrollment of students entering the Science stream has also not reached 60 percent. The iV-STEM KIT product that was created coincides with the current situation because this product can attract students' interest in subjects related to the STEM field. Not only that, this STEM KIT can make it easier for the school to prepare materials and carry out 'Hands-on Experience' activities with the students. This iV-STEM KIT product is produced using materials that are easily available around at a low cost. Parents can also save and only need to buy one unit of this iV-STEM KIT for one price without buying at a high cost for some necessary materials. This iV-STEM KIT has used a digitization method in the operation of using this STEM Kit. Bar codes have been provided to facilitate users to carry out this magic balloon activity. The users just need to scan the barcode and they will be able to see the video recording that has been prepared by the researchers on the official iV-STEM YouTube. This iV-STEM KIT is an innovative and creative teaching aid to increase the level of understanding of students in the STEM field because it is cheap and easy to do anywhere. This product has been commercialized to schools, parents and the public as a teaching aid for Science subjects in the STEM field.